Observation of two-center interference effects for electron impact ionization of N2. (26th June 2015) - Chaluvadi, Hari; Ozer, Zehra Nur; Dogan, Mevlut; Ning, Chuangang; Colgan, James; Madison, Don
Abstract: In 1966, Cohen and Fano (1966 Phys. Rev. 150 30 ) suggested that one should be able to observe the equivalent of Young's double slit interference if the double slits were replaced by a diatomic molecule. This suggestion inspired many experimental and theoretical studies searching for double slit interference effects both for photon and particle ionization of diatomic molecules. These effects turned out to be so small for particle ionization that this work proceeded slowly and evidence for interference effects were only found by looking at cross section ratios. Most of the early particle work concentrated on double differential cross sections for heavy particle scattering and the first evidence for two-center interference for electron-impact triple differential cross section (TDCS) did not appear until 2006 for ionization of H2 . Subsequent work has now firmly established that two-center interference effects can be seen in the TDCS for electron-impact ionization of H2 . However, in spite of several experimental and theoretical studies, similar effects have not been found for electron-impact ionization of N2 . Here we report the first evidence for two-center interference for electron-impact ionization of N2 .